A CASE STUDY ON ANJANANAMIKA W.S.R TO STYE (AYUSHDHARA, 2020)
Stye is an infection of the sebaceous glands of zeis at the base of the eye lashes, or an infection of the apocrine glands of moll. In Ayurvedic science, based on clinical signs and symptoms, stye can be correlated to Anjananamika where the symptoms include Dahatodavatitamrapidaka– i.e., boil which will be in Tamravarna associated with burning sensation and pricking sensation at Vartmapradesha i.e., in the lid and the other symptoms includes Mridvimandaruja– it will be soft and associated with mild pain. The line of treatment of the disease Anjananamika (stye) includes Swedana (hot compress), Nishpidana (pressure applying to drain out pus), Bhedana (incision), Pratisarana (rubbing of medicaments over the lids), Anjana (collyrium). The objective of the present study is to evaluate the effect of Bidalaka and Aschyotana along with internal medicines. A 19-year female patient approached the Shalakya tantra OPD of Sri Paripoorna Sanathana Ayurveda Medical College, Hospital and Research centre, Nelamangala, Bangalore with the complaints of swelling in the left eye lid since 3 days with mild pain and redness of the eyes. On examination, the whole edge of the left eye lid was oedematous along with the presence of an abscess in outer canthus. On these signs and symptoms, the patient was diagnosed as a case of stye and advised Kriyakalpa based on the Roga and Rogibala along with internal medicines which have given promising results with the complete absence of the symptoms within 10 days.